Ung medvirkning Kreativitet og konflikt i planlegging - Hagen, Aina Landsverk; Andersen, Bengt (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
How should we go about collaborating with children and adolescents? Young Participation: Creativity and Conflict in Planning explores how youth participation work in practical terms, in the context of urban development processes at the municipal level in Norway. From their unique perspectives, several social scientists, artists, an architect, and a young contributor discuss experiences and dilemmas of including children, teens, and young adults as contributing stakeholders on various projects. The reader will find concrete examples of participation processes and tools developed in cooperation with young people, architects, and public employees. The chapters reveal how good intentions regarding inclusion can obscure power hierarchies, friction, and conflicts of interest. Yet they also demonstrate that the potential for creativity and innovation are great when young people are invited to contribute their input in planning and developing everything from youth community centers and school grounds to parks and other outdoor spaces in local neighborhoods. This anthology will provide inspiration to researchers, students, municipal employees, urban planners, and others working collaboratively in urban and community development. Among the topics covered are participation as co-research, social entrepreneurship and participation as part of school curricula and in socio-cultural place analyses, the power of the hand in creative practices, co-location as a trend, digital and hybrid participation processes, and power plays in planning. By introducing a new model for 'thick participation', the anthology attempts to ensure that young citizens are not just seen and heard but are also given the opportunity to become lasting resources within their local communities. The book's editors, senior researcher Aina Landsverk Hagen and research professor Bengt Andersen, are both based at the Work Research Institute (AFI), Oslo Metropolitan University.